2020
DOI: 10.2147/dddt.s247103
|View full text |Cite
|
Sign up to set email alerts
|

<p>Emodin Protects Against Acute Pancreatitis-Associated Lung Injury by Inhibiting NLPR3 Inflammasome Activation via Nrf2/HO-1 Signaling</p>

Abstract: Lung injury is a common complication of acute pancreatitis (AP), which leads to the development of acute respiratory distress syndrome and causes high mortality. In the present study, we investigated the therapeutic effect of emodin on AP-induced lung injury and explored the molecular mechanisms involved. Materials and Methods: Thirty male Sprague-Dawley rats were randomly divided into AP (n=24) and normal (n=6) groups. Rats in the AP group received a retrograde injection of 5% sodium taurocholate into the bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 37 publications
4
40
0
Order By: Relevance
“…Our novel data indicated that emodin ameliorated the severity of SAP-ALI by through inhibiting the CIRP-related signaling and decreased neutrophil infiltration in the lung of rats by attenuating the CIRP-induced IL-1β-dependent CXCL1 expression. A previous study has showed that emodin can relieve SAP-associated lung injury by inhibiting the activation of NLRP3 inflammasome (Gao et al, 2020). Our study also indicated that emodin reduced cell pyroptosis and IL-1β production as well as CXCL1 expression by inhibiting the activation of NLRP3 inflammasome induced by CIRP, which may be the key mechanism underlying the action of emodin in reducing SAP-ALI severity in rats.…”
Section: Discussionsupporting
confidence: 73%
“…Our novel data indicated that emodin ameliorated the severity of SAP-ALI by through inhibiting the CIRP-related signaling and decreased neutrophil infiltration in the lung of rats by attenuating the CIRP-induced IL-1β-dependent CXCL1 expression. A previous study has showed that emodin can relieve SAP-associated lung injury by inhibiting the activation of NLRP3 inflammasome (Gao et al, 2020). Our study also indicated that emodin reduced cell pyroptosis and IL-1β production as well as CXCL1 expression by inhibiting the activation of NLRP3 inflammasome induced by CIRP, which may be the key mechanism underlying the action of emodin in reducing SAP-ALI severity in rats.…”
Section: Discussionsupporting
confidence: 73%
“…A number of studies investigating the anti-inflammatory potential of emodin have also been reported (27,28). However, the functional involvement of emodin in neutrophil recruitment and IL-1β secretion through inflammasome regulation has not been reported in SAP-induced ALI in vivo (29). On the other hand, dexamethasone (DEX) is an important glucocorticoid that is vital in anti-inflammation and anti-toxicity, and can be used to alleviate early inflammatory reactions in the lungs in SAP (30).…”
Section: Emodin Ameliorates Acute Pancreatitis-induced Lung Injury By Suppressing Nlrp3 Inflammasome-mediated Neutrophil Recruitmentmentioning
confidence: 99%
“…Histopathological analysis. Histopathological analysis was performed in accordance with a previously published method (29). Briefly, tissue samples obtained from the right upper lobe and from the pancreas were fixed in 4% paraformaldehyde solution for 24 h at room temperature and then embedded in paraffin.…”
Section: Animalsmentioning
confidence: 99%
“…Studies have found that the activation of Nrf2 and induction of HO-1 could inhibit the NLRP3 inflammasome and thus pyroptosis. [16][17][18] Activation of the Nrf2 pathway with isorhamnetin reduces the inflammatory response of HGFs. 19 These findings promote speculation that the activation of Nrf2/HO-1 may be a protection mechanism in periodontitis and reduce pyroptosis.…”
Section: Introductionmentioning
confidence: 99%